PENINGKATAN KREATIVITAS DAN PRESTASI BELAJAR IPA MELALUI PROJECT BASED LEARNING PADA SISWA KELAS VIII - Hariyanto Dwi Cahyo (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2023)
This class action research aims to determine whether there is an increase increativity and achievement in science learning through Project Based Learning in class VIII D of SMP Negeri 2 Ngemplak semester gasal academic year 20 22/2023. The subjects of this class action research were 3 2 students of grade VIII D of SMP Negeri 2 Ngemplak. This research is designed classroom action research and is carried out in two cycles with each cycle consisting of four stages, namely action planning, action implementation, observation and evaluation, and analysis and reflection. Each cycle is carried out with three meetings and each meeting is 2 x 40 minutes. The implementation of research is carried out together with students, and other science subject teachers. The data collection techniques used are observation, test and documentation techniques. The success target of this class action research is that as many as 24 students have shown creativity during learning activities and achieved a KKM score of 72. Based on the results of the research that has been carried out, it can be concluded that there is an increase in creativity and science learning achievement of grade VIII D students of SMP Negeri 2 Ngemplak in the first semester of the 2022/2023 academic year through Project Based Learning. From the data on the results of research that has been carried out shows an increase in student creativity and science learning achievement from 1.6 students (5.0%) who are creative and complete in the initial condition increased to 2.4 students (7.5%) who are creative and completed after the action of cycle I. At the end of the second cycle of action increased to 31 students (97%) who achieved creative and reached the limit of learning completeness. The average score of science learning achievement also increased from 69.53 in the pre-cycle to 75.47 (an increase of 9%) after the first cycle action and to 84.69 (an increase of 2.2%) after the second cycle action.